RECRUITMENT OF WINTER TICKS (DERMACENTOR ALBIPICTUS) IN CONTRASTING FOREST HABITATS, ONTARIO, CANADA - Addison, E. M.; McLaughlin, R. F.; Addison, P. A.; Smith, J. D. (Lakehead University, 2016)
Recruitment of winter tick larvae (Dermacentor albipictus) was studied in a forest opening and a closed canopy deciduous forest to evaluate their potential as sources of tick infestation to moose (Alces alces). Engorged female ticks were set out in early May at each site and monitored to measure the proportions of females producing larvae and the number of larvae recruited per g of surviving female. Recruitment was higher in the forest during the hotter, drier summer of 1983, primarily due to fewer engorged females producing larvae in the opening, and was much higher (>2 x) in the opening during the cooler, damper summer of 1984. Recruitment in the field was 20–40% of that under laboratory conditions. Desiccation of eggs and/or larvae was the probable cause for the annual variation in recruitment in the opening. Most larvae were recruited earlier in the opening than in the forest site. Neither weight nor date of detachment of engorged female ticks influenced when larvae first ascended vegetation. Weather, especially temperature, and site structure and composition affect abundance of the free-living stages of the winter tick and larvae available for transmission to moose. Open sites should support more winter tick larvae than densely forested sites except in years of particularly hot and dry weather.